Uso de modflow para simulação da hidrodinâmica de meios porosos em wetlands construídos - Fioreze, Mariele (2017)
Constructed wetlands (CWs) are artificial systems used for wastewater treatment, whose objective is to reproduce, under controlled conditions, the treatment mechanisms that occur in natural environments, through the exploration and improve the processes that involve the vegetation, porous media and microbial assemblages. Horizontal subsurface flow constructed wetlands (HSSF-CWs) is characterized by flow in a horizontal direction, in a gravel or sand beds planted or unplanted with emergent macrophytes whose the inlet and outlet are horizontally opposed, which allows the wastewater flow through the rhizosphere and have contact with the biofilm formed in subsurface. Traditional studies about CWs focuses on the efficiency of contaminants removal look at systems as a "black-boxes" from empirical approaches and do not distinguish between the different active removals processes. The development of numerical models, in order to helping to identify and improve the role of each element acting in the treatment, whether the properties of the porous media, constructive geometry, flow characteristics, among others, appears as an alternative to reach a more detailed understanding of the internal processes involved in CWs. In general, numerical models consist of governing equations (derived from the mathematical combination of the water balance and Darcy's law), initial conditions (they refer to the distribution of the hydraulic head in the model domain) and boundaries conditions (define the hydraulic or physical boundaries that delimit the model domain). In the last decade, different 1D and 2D numerical models have been developed and applied for the simulation of subsurface flow CWs under conditions of saturated horizontal flow (CWM1-RETRASO and PHWAT), variably saturated vertical flow (FITOVERT and HYDRUS-CW2D) and vertical or horizontally saturated flow (HYDRUS-CWM1). However, few studies regarding the application of 3D numerical models for CWs simulation are reported in the scientific literature. In this study, the hydrodynamic simulation of the porous media in a horizontal subsurface flow constructed wetland was run through the application of a 3D numerical model. The flow patterns were simulated according to the project design and scenarios with changes in the porous media hydrodynamic (hydraulic conductivity) and in the positioning of the wastewater distribution mechanisms (distribution along the cross section with two pipes) in order to verify the influence of these factors in the flow pattern and also to indicate advantages and disadvantages that contribute to the design. The softwares MODFLOW and MODPATH, in the GMS family code, were used for to simulate the direction and flow velocity, hydraulic head and pathlines. The model proved to be a powerful tool to simulation, allowing observing the interdependence between the hydrodynamic parameters and the hydraulic characteristics in the porous media. The simulated scenarios showed the possibility of improving the flow patterns, mainly using two pipes to distribute the wastewater in a more homogeneous way along the cross section of the bed. The use of a porous media with lower hydraulic conductivity also showed improvement in flow characteristics evaluated. However, the general context of wastewater treatment facilities (pretreatment units and tributary loads) should be considered, since materials with low hydraulic conductivity are more susceptible to clogging. Proper design is crucial to improving the treatment conditions in the HSSF-CWs and also to avoid the occurrence of hydraulic problems and damage to the treatment, such as the clogging.